PENTINGNYA POLA KEMITRAAN DALAM RANGKA MENINGKATKAN PERAN DAN KINERJA USAHA MIKRO, KECIL, DAN MENENGAH DI JAWA TIMUR PERIODE 2006 – 2011 - Wanda Marsa Widyani (CALYPTRA, 2014)
Micro, Small and Medium Enterprises has a large role in the economy of the people in East Java , and UMKM development efforts in East Java has been done , either by the central government , provincial, district , city , state , and local enterprises . Problems faced by UMKM is still structurally encompasses so many UMKM are actually feasible but not bankable . To overcome these problems, one of the efforts that can be done is through " Business Partnership " between UMKM with relevant parties , so expect through business partnerships can quickly bersimbiose mutualistic. In an effort to make the development of business partnerships between UMKM in order to increase the role and performance of UMKM to the economy of East Java used SWOT analysis . Partnerships in the development of UMKM is very helpful so UMKM can continue to innovate and develop products so that the results generated UMKM can compete with domestic products and international products. The findings of this study that the UMKM have to use a partnership as a business model , but for UMKM with limited resources management not to use as a reference SWOT strategy business steps . Keywords : UMKM , SWOT , Partnership.